Consumo y costo de ceftazidima en pacientes hospitalizados en los servicios del hospital iv víctor lazarte echegaray-essalud en el año 2008”. - Poma Vidal, Jorge Luis (2009)
This research paper is a descriptive, cross-sectional and retrospective study aimed at determining consumption and costs in the Ceftazidime Inpatient Services (Medicine, Surgery, Gynecology, Obstetrics, Intensive Care Unit and Intermediate Care Unit) Hospital IV Víctor Lazarte Echegaray-ESSALUD in 2008 The sample universe was composed of monthly records of hospitalized patients with computerized prescription Ceftazidime served by the Hospital Pharmacy through the unit dose system (SISMUD). For this, whe took the consumption data of Hospital Management System Hospital IV Victor Lazarte Echegaray, in the period from 1erst January to 31th December 2008, these data processed and analyzed in an Excel spreadsheet, drawing general parameters of the annual consumption of services. We used the defined daily doses (DDD) for the determination of Ceftazidime consumption in the adult inpatient services Hospital Víctor Lazarte Echegaray IV, which was 4.74 DDD/100camas/día annual cost. The annual expenditure for the Hospital Ceftazidime IV-Víctor Lazarte Echegaray ESSALUD was S/.92502.78